Effect of taping on ground reaction forces and comfort level in flat-footed female recreational runners - Koh, Alvina Hui Li (2018)
Background – Low-arched feet (flat-feet) is a factor that may increase the risk of sustaining lower extremity injuries in recreational running. Some studies have shown that anti-pronation taping reduces pronation of the foot and potentially lowers the risk of injury. However, few have explored important parameters such as ground reaction force (GRF) and comfort level. Purpose – The purpose of this study was to determine the effect of low-dye tape on GRF and comfort level of participants. Methods – A within-subject, randomised crossover design was adopted. 13 female participants were screened and those who fulfilled the criteria were deemed flat-footed and eligible. They underwent two taping conditions - sham taping and low-dye taping, before completing a comfort level visual analog scale. Participants ran on an instrumented treadmill, at three different jogging speeds, where data on GRF variables were collected. A two-way repeated measures ANOVA was used to compare GRF variables between conditions and across the speeds. A paired t-test was used to compare comfort levels. Results – All GRF variables measured showed no significant differences between the two taping conditions (p > 0.05). However, significant differences in stance time (p < 0.05) and comfort level (p < 0.001) was observed. Significant differences for all variables were present across the three speeds (p < 0.05). Conclusion – Low-dye tape has no effect on GRF but has an effect on comfort level. Future studies should consider collecting kinematic variables alongside GRF and may consider adopting a more comfortable taping technique with similar ability to reduce foot pronation.